2010
DOI: 10.1021/jp1018372
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Emission of Monolayer-Protected Au38 Clusters

Abstract: Emission spectra are presented for Au 38 clusters in the temperature regime between 4 and 300 K. At room temperature, a broad emission band around 1.35 eV is observed. Upon cooling, fine structure appears that reveals the presence of at least four emission bands. The lowest energy emission band is resonant with the highest occupied molecular orbital-lowest unoccupied molecular orbital energy gap for Au 38 clusters. We propose that the higher emission energy bands result from emission from higher excited states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 28 publications
6
45
3
Order By: Relevance
“…3, 19 At 500 nm, corresponding to the weak blue band centered at 470 nm, the fluorescence exhibits a lifetime of 2.5 ns. This is different from that reported by Devadas et al in which they found as fast as 100 fs decay in Au 25 (C 6 S) 18 and Au 25 (GS) 18 in the blue band. 15 This likely is due to the influence of different ligand.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…3, 19 At 500 nm, corresponding to the weak blue band centered at 470 nm, the fluorescence exhibits a lifetime of 2.5 ns. This is different from that reported by Devadas et al in which they found as fast as 100 fs decay in Au 25 (C 6 S) 18 and Au 25 (GS) 18 in the blue band. 15 This likely is due to the influence of different ligand.…”
Section: Resultscontrasting
confidence: 99%
“…11 The optical properties of Au 25 NCs have been studied by various techniques, 8,12 such as femtosecond laser pump−probe techniques, 13,14 ultrafast upconversion luminescence, 15,16 and temperature dependence. 17, 18 Zhu and co-workers have correlated the structure with the optical transitions. 8 Link et al observed two luminescence bands at 1.5 and 1.15 eV in glutathione-protected Au 28 NCs and assigned to fluorescence and phosphorescence, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the conventional techniques, such as steady‐state fluorescence and absorption,[11b], ultrafast, time‐resolved,[41a], as well as temperature‐dependent fluorescence and absorption are also used to provide the insight to identify the characteristic of NCs. [7g],[12a,b],…”
Section: Optical Properties Of Gold Nanoclustersmentioning
confidence: 99%
“…Furthermore, it has been shown that ligands can significantly affect the emission spectrum, both the peak position and the spectrum shape. [12c], Luminescence of Au 25 NCs was observed by many groups and different fluorescent wavelengths were found between 640 and 750 nm protected by various ligands, such as bovine serum albumin (BSA) at 640 nm and 674 nm, phenyl ethane thiol at 750 nm,[11a] glutathione at 700 nm,[41a] human serum albumin (MSA) at 700 nm,[43c] pepsin at 670 nm, and dihydrolipoic acid (DHLA) at 684 nm . It is noteworthy that the glutathione‐coated Au 25 NCs exhibit slightly different emissions for synthesized by different methods.…”
Section: Optical Properties Of Gold Nanoclustersmentioning
confidence: 99%
“…In previous PL studies, a red or near-infrared (NIR) emission, centered from 610 to 920 nm, was observed for Au 38 [15], Au-BSA [14], Au 55 [16], Au(I)-thiolate complex [17], and Au 25 (SG) 18 nanoclusters [5,18]. This red band was suggested to be associated with the ligand [16,19].…”
Section: Discussionmentioning
confidence: 90%